2012
DOI: 10.1007/s10548-012-0270-x
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Correlation of Impulsivity in Medial Prefrontal Cortex

Abstract: Impulsivity is a complex behaviour composed of different domains encompassing behavioural disinhibition, risky decision-making and delay discounting abnormalities. To investigate regional brain correlates between levels of individual impulsivity and grey matter volume, we performed voxel-based morphometric correlation analysis in 34 young, healthy subjects using impulsivity scores measured with Barratt Impulsivity Scale-11 and computerized Kirby's delay discounting task. The VBM analysis showed that impulsivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
126
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(149 citation statements)
references
References 75 publications
(82 reference statements)
19
126
4
Order By: Relevance
“…Moreover, more impulsive individuals exhibited greater activity in the ventral striatum and less activity in the frontomedial cortex, a finding that mirrors the differential volumetric findings in the present study. Only a handful of studies have used structural neuroimaging to search for brain correlates of temporal discounting (52)(53)(54). These studies found that greater impulsivity was significantly correlated with striatal and frontal cortical gray matter volume in partial agreement with the present findings.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, more impulsive individuals exhibited greater activity in the ventral striatum and less activity in the frontomedial cortex, a finding that mirrors the differential volumetric findings in the present study. Only a handful of studies have used structural neuroimaging to search for brain correlates of temporal discounting (52)(53)(54). These studies found that greater impulsivity was significantly correlated with striatal and frontal cortical gray matter volume in partial agreement with the present findings.…”
Section: Discussionsupporting
confidence: 88%
“…Many studies have revealed significant correlations between impulsivity and structures or functions of multiple gray matter regions in healthy subjects (Boes et al, 2009;Brown, Manuck, Flory, & Hariri, 2006;Cho et al, 2013;Dambacher et al, 2015;Farr, Hu, Zhang, & Li, 2012;Gardini, Cloninger, & Venneri, 2009;Matsuo et al, 2009;Muhlert & Lawrence, 2015;Schilling et al, 2012Van den Bos, Rodriguez, Schweitzer, & McClure, 2015). In the past few years, diffusion tensor imaging (DTI) technique shows great promise to evaluate the integrity of white matter (WM) tracts in human brain , and the white matter (WM) integrity of the bilateral frontal and temporal lobes was negatively associated with impulsivity in healthy adolescents (Olson et al, 2009).…”
mentioning
confidence: 99%
“…a negative correlation between grey matter volume within right ventromedial prefrontal cortex and impulsivity derived measures using the Pediatric Behavior Scale (PBS). Few years later, [5] showed in young people (age 23.4 ± 4.3 yrs.) a positive correlation between grey matter volume within the same brain region and impulsivity scores measured with the Barratt Impulsivity Scale-11 (BIS) and a computerized delay discounting task.…”
Section: Introductionmentioning
confidence: 99%
“…For over a while, impulsivity disorders have been associated with gray matter abnormalities in prefrontal cortex and striatal aspects [3][4][5][6]. One type of functional architecture has posited that striatal regions encode the current value of tangible rewards, whereas prefrontal regions represent more abstract rewards and long-term goals; although this view is certainly changing as we gain more knowledge [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation